Uranium in drinking-water: A unique case of guideline value increases and discrepancies between chemical and radiochemical guidelines. (April 2015) - Ansoborlo, Eric; Lebaron-Jacobs, Laurence; Prat, Odette
Abstract: Background: Uranium represents a unique case for an element naturally present in the environment, as its chemical guideline value in drinking water significantly increased from 2 μg/L in 1998 up to 15 μg/L in 2004 and then to 30 μg/L in 2011, to date corresponding to a multiplication factor of 15 within a period of just 13 years. Objectives: In this commentary we summarize the evolution of uranium guideline values in drinking-water based on both radiological and chemical aspects, emphasizing the benefit of human studies and their contribution to recent recommendations. We also propose a simpler and better consistency between radiological and chemical values. Discussion: The current chemical guideline value of 30 μg/L is still designated as provisional because of scientific uncertainties regarding uranium toxicity. During the same period, the radiological guideline for 238 U increased from 4 Bq/L to 10 Bq/L while that for 234 U decreased from 4 Bq/L to 1 Bq/L. These discrepancies are discussed here, and a value of 1 Bq/L for all uranium isotopes is proposed to be more consistent with the current chemical value of 30 μg/L. Conclusion: Continuous progress in the domains of toxicology and speciation should enable a better interpretation of the biological effects of uranium in correlation with epidemiological human studies. This will certainly aid future proposals for uranium guideline values. Highlights: Uranium in drinking-water: a unique case of guideline value increases We summarize the evolution of uranium guideline values in drinking-water. We discuss discrepancies for uranium between chemical and radiological guidelines. We describe recent progress in the domains of toxicology and speciation.